The effects of virtual behavior skills training (BST) in improving behavioral strategies of parents used in applied behavior analysis (ABA) sessions - Urbano, Kimberly Ann C. (Animo Repository, 2022)
Families during COVID-19 Pandemic have limited access to evidence-based behavioral intervention for children with autism spectrum disorder. Using virtual parent training as a substitute for in-person parent training, the current study investigated the effects of behavior skills training on behavioral strategies of three parents to implement Applied Behavior Analysis (ABA) strategies with their children with autism. In this action research, parents increased their knowledge across the trained behavioral strategies by 66% and improved their implementation of behavioral strategies with their children by 72.17% on reinforcement, 95.5% on prompting, 56.9% on pivotal response training, and 78% on discrete trial training. Improvements in the training program are discussed.